How Effective Principal Communication Drives Staff Performance: Robust Evidence from a Regression Study in a Pharmacy Vocational School - Fitiani, Hesti; Irawati, Irawati; Setyaningsih, Rini; Iskandar, Edi; Rahmatullah, Mamat (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
Effective communication is widely recognized as a core driver of educational leadership, yet its direct impact on staff performance remains underexplored in vocational school settings. This study seeks to provide compelling empirical evidence on how principal communication effectiveness contributes to measurable improvements in educational staff performance at a Pharmacy Vocational High School in Indonesia. Using a quantitative design, simple linear regression was applied to data collected from all 73 educational staff through a total sampling approach. The analysis examined the predictive power of principal communication effectiveness on staff performance outcomes. The results reveal a strong, statistically significant effect, with principal communication accounting for 71.4% of the variance in staff performance (R² = 0.714). A robust positive correlation was also observed (r = 0.845, p = 0.005), indicating that staff performance tends to increase substantially when leadership communication improves. The findings underscore the strategic importance of communication-centered leadership in strengthening school performance. By showing that a single leadership variable decisively contributes to staff effectiveness, this study highlights the need for educational institutions—especially vocational schools—to invest in sustained capacity-building in communication for school leaders. Future research is encouraged to explore complementary leadership factors that can further optimize performance outcomes.